Inpatient hospital use in the frst year after release from prison: A Western Australian population-based record Linkage study - Alan, Janine; Burmas, M.; Preen, D.; Pfaff, J. (2011)
Objective: To describe three aspects of inpatient use for ex-prisoners within the frst 12 months of release from prison: the proportion of released prisoners who were hospitalised; the amount of resources used (bed days, separations and cost); and the most common reasons for hospitalisation. Methods: Secondary analysis of wholepopulation linked prison and inpatient data from the Western Australian Data Linkage System. The main outcome measure was frst inpatient admission within 12 months of release from prison between 2000 and 2002 and related resource use. Results: One in fve adults released from Western Australian prisons between 2000 and 2002 were hospitalised in the 12 months that followed, which translated into 12,074 inpatient bed days, 3,426 separations and costs of $10.4 million. Aboriginals, females and those released to freedom were most at risk of hospitalisation. Mental health disorders such as schizophrenia and depression, and injuries involving the head or face and/or fractures, accounted for 58.9% of all bed days. Ex-prisoners were 1.7 times more likely to be hospitalised during a year than Western Australia's general adult population of roughly the same age. Conclusions: Using whole-population administrative linked health and justice data, our fndings show that prisoners are vulnerable to hospitalisation in the 12-month period following their release from prison, particularly Aboriginals, females and those with known mental health problems. Implications: Further research is needed to assess whether contemporary services to support community re-entry following incarceration have led to a measurable reduction in hospital contacts, especially for the subgroups identifed in this study. © 2011 The Authors. ANZJPH © 2011 Public Health Association of Australia.